2023
DOI: 10.3389/fimmu.2023.1107639
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of national standard for anti-SARS-Cov-2 neutralizing antibody in China: The first National Standard calibration traceability to the WHO International Standard

Abstract: Neutralizing antibody (NtAb) levels are key indicators in the development and evaluation of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccines. Establishing a unified and reliable WHO International Standard (IS) for NtAb is crucial for the calibration and harmonization of NtAb detection assays. National and other WHO secondary standards are key links in the transfer of IS to working standards but are often overlooked. The Chinese National Standard (NS) and WHO IS were developed by China and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…For pseudovirus assays, the total GMTs were 371.8 (PV-HIV) and 519.2 (PV-VSV). In a research project to establish the National Standard for anti-SARS-CoV-2 nAbs in China, which can be traced back to the WHO International Standard [140], six laboratories used the live virus PRNT and CPE methods, and four laboratories used the pseudovirus PV-VSV method. The co-calibration results of the two candidate standards showed that using the wild-type strain, the GMTs of samples detected using the live virus method were 133 and 194, and the GMTs of samples detected by the pseudovirus method were 641 and 1512.…”
Section: Correlation Analysis Of Testing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For pseudovirus assays, the total GMTs were 371.8 (PV-HIV) and 519.2 (PV-VSV). In a research project to establish the National Standard for anti-SARS-CoV-2 nAbs in China, which can be traced back to the WHO International Standard [140], six laboratories used the live virus PRNT and CPE methods, and four laboratories used the pseudovirus PV-VSV method. The co-calibration results of the two candidate standards showed that using the wild-type strain, the GMTs of samples detected using the live virus method were 133 and 194, and the GMTs of samples detected by the pseudovirus method were 641 and 1512.…”
Section: Correlation Analysis Of Testing Methodsmentioning
confidence: 99%
“…However, the diversity of testing protocols hinders direct comparisons among the different study results. Neutralizing antibody levels are important indicators of vaccine effectiveness and are critical for therapeutic and seroepidemiological studies [116,140]. The accuracy, comparability, and reliability of different types of neutralizing antibody assays are of great importance in vaccine development, production, and application.…”
Section: Standardization Of Neutralizing Antibody Detection Methodsmentioning
confidence: 99%
“…The World Health Organization (WHO) has established the first and second International Standards (IS) for anti-SARS-CoV-2 immunoglobulin (Lot: 20/136, 21/340) [ 10 , 11 ]. In addition, China has established the first and second National Standards for neutralizing antibodies against SARS-CoV-2 (Lot: 280034-202001, 280034-202102) [ 12 , 13 ]. These standards provide a foundation for the accurate and comparable detection of SARS-CoV-2 NtAbs, thereby facilitating the development and application of COVID-19 vaccines and antibody-based drugs worldwide [ 14 ].…”
Section: Introductionmentioning
confidence: 99%